COMPARATIVE ANALYSIS OF CONSUMER SWITCHING BEHAVIOR BETWEEN BANK NEGARA INDONESIA AND BANK RAKYAT INDONESIA - Manurip, Jelita; Tumbuan, Willem J.F.A; Worang, Frederik G. (Universitas Sam Ratulangi, 2020)
Switching behavior is abandoning a product or services in favor of a competitor. The background of this research is to compare how is the customers’ responses to the service that the banks gives to them due to high competition between the bank nowadays and the purpose are to know about the switching behavior between the banks which are Bank Negara Indonesia and Bank Rakyat Indonesia in Manado and Bitung. This research is a quantitative type of research, which uses primary data obtained through questionnaires and uses independent sample t-test as the analytical tool to find out if there is a significant difference in consumer switching behavior based on 5 different indicators which are price, reputation, distance, advertisement, and service quality. The population of this research is all the customers of Bank Negara Indonesia and Bank Rakyat Indonesia in Manado and Bitung as a developing city in North Sulawesi province, and the sample size is 100 of BNI’s customers and 100 of BRI’s customers. So the total is 200 respondents in Manado and Bitung. The result of this research showed that 3 indicators had no significant difference between the two banks and as recommendation BNI should improve their service to the rural areas especially in Manado, Bitung and surrounding. Keyword: consumer switching behavior, independent sample t-test.